Evaluation of the location of distribution center company AES Sul distribuidora gaucha power towards regional deposits - Rosa, Iriane; Abreu, Ivonisa; Pedrozo, Ivonete (Revista de Administração da UFSM, 2016)
Companies that provide services basic as distribution of energy electric should keep the continuity of services independent of situation because they are necessary to provide the terms minimal for the life in society. The intention this study is create an analysis on the location of distribution center of materials of concessionaire AES Sul Distribuidora Gaúcha de Energia, today located in city of Esteio, Rio Grande do Sul. Was evaluated what the place, within of his field of concession, can attend the deposits regional with higher quality. This review becomes necessary, because the delay for the delivery the materials used in its units regional back delays in recovery of network of distribution of energy electric or lag in attendance of new installation both residential as industrial. For this review are related them variables of consumption and time of attend through of methodologies of center of gravity and of units of emergencies. After the enforcement of methodology proved that the region central of his area of concession is the region more adequate for de mounting of his units of distribution of materials.